2012
DOI: 10.1093/heapro/das022
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement: a practical measure for workplace health promotion?

Abstract: The objectives of this study were to investigate whether psychological job demands, personal control and social support affect the negative health measure of depression differently than the positive measure of work engagement and to investigate whether work engagement mediates the effects of job demands and resources on the level of depression. We discuss the implications of using engagement as an outcome measure in workplace health promotion. We performed a cross-sectional questionnaire study among a general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 42 publications
2
36
1
3
Order By: Relevance
“…Work engagement, as opposed to burnout, is an emerging concept in contemporary occupational health science and promotion of work engagement may lead to greater improvement in work performance than the traditional sole focus on disease prevention [1]. The concept of employee engagement represents a new approach to occupational health in which researchers are not only interested in what the causes of work related diseases are but also why people stay healthy and flourishing in a workplace [2].…”
Section: Three-factorial Model Of Work Engagementmentioning
confidence: 99%
“…Work engagement, as opposed to burnout, is an emerging concept in contemporary occupational health science and promotion of work engagement may lead to greater improvement in work performance than the traditional sole focus on disease prevention [1]. The concept of employee engagement represents a new approach to occupational health in which researchers are not only interested in what the causes of work related diseases are but also why people stay healthy and flourishing in a workplace [2].…”
Section: Three-factorial Model Of Work Engagementmentioning
confidence: 99%
“…A study among a general working population in Norway, Torp, Grimsmo, Hagen, Duran, and Gudbergsson (2013) first investigated whether psychological job demands, personal control, and social support affect the negative health measure of depression differently than the positive measure of work engagement. The study showed that high control and social support were associated with a low score on depression and a high score on engagement.…”
Section: Job Demands Control and Support-a Salutogenic Pathwaymentioning
confidence: 99%
“…The effectiveness of MHP interventions has been well documented in school settings (Barry et al, 2013;Evans et al, 2005;Franze, 2004;Michaelsen-Gartner and Witteriede, 2009;Mishara and Ystgaard, 2006;Roberts et al, 2003;Weare and Nind, 2011), at the workplace (Czabala et al, 2011;Lerner et al, 2013;Mattke and Van Busum, 2013;Patel et al, 2013;Sun et al, 2013;Torp et al, 2013;Tsutsumi et al, 2009), and in community centers serving older adults (Chapin et al, 2013;Forsman et al, 2011;Ichida et al, 2013). This is in line with the results of a recent systematic review (Mcdaid and Park, 2011) and a report presenting different economic models for mental health promotion and prevention (Knapp et al, 2011).…”
Section: Introductionmentioning
confidence: 99%